Growth Performance, Biochemical Parameters, and Cost-benefit Analysis of the African Catfish (Clarias gariepinus) Juveniles Fed Diets with Varying Levels of Orange Fleshed Sweet Potato (Ipomoea batatas) Peels - (:unkn) unknown (My University, 2025)
The current high cost of conventional energy feedstuffs used in fish feeding due to its global scarcity and fierce human vs. animal competition calls for united effort towards finding alternatives, cost-effective and sustainable aquaculture feed. The experiment was conducted for 16 weeks to examine the effect of the supplementation of orange fleshed sweet potato peels in Clarias gariepinus juveniles' diet. There were 6 treatments ([Control; 0%], 20%, 40%, 60%, 80%, 100% inclusion) with 3 replicates each, for a total of 18 tanks. All tanks were stocked with 10 fish (initial mean weight of 6.64 ± 0.01g).to study the effect of dietary inclusion of orange fleshed sweet potato peels on growth performance and biochemical profiles of C. gariepinus juveniles. Fish were fed 5% of their body weight twice daily, and water quality was analyzed by standard procedure. Results indicated a significant difference in growth performance, feed utilization and biochemical profiles between the control and treatment groups (P<0.05). Control diet (D1) recorded the highest mean weight gain (MWG) (169.80±2.21) and specific growth rate (SGR) (1.19±0.00), and the diet with 100% orange fleshed Ipomea batatas peels (D6) recorded the lowest mean weight gain MWG (112.34±0.48) and SGR (1.05±0.00). Biochemical analysis indicated there is significant differences(P<0.05) among treatment groups and control. Serum glucose and creatinine increased with increasing percentage of inclusion of orange fleshed Ipomea batatas peel, but globulin, albumin, total protein, and electrolytes (potassium and sodium) decreased. Economic study indicated that feed cost was significantly reduced with inclusion of orange fleshed Ipomea batatas peel in the feed, and 100% orange fleshed Ipomea batatas peel diet showed highest margin of profit. This study concludes that, inclusion of orange fleshed Ipomea batatas peel in Clarias gariepinus juveniles’ diet is cost-effective, especially
Keywords: African Research